Recruitment limitation in secondary forests dominated by an exotic tree - Lichstein, Jeremy W. (2004)
Question- What factors limit woody plant recruitment in a mosaic landscape where former agricultural lands are dominated by the invasive tree, Ligustrum lucidum W. T. Aiton (Oleaceae)?  Location- Subtropical northwestern Argentina. Methods- In secondary forest patches, we measured (1) tree, shrub, and liana abundance in different size classes (stems ¡Ý 25 cm tall); (2) seed rain of Ligustrum and two native trees; and (3) topographic, soil, and light variables.  We used spatial autoregressive models to test for effects of Ligustrum canopy dominance and environmental variables on native plant abundance in each size class.  We used multiple regression on resemblance matrices to quantify the relative importance of spatial (e.g., dispersal) and environmental effects on native species composition. Results- Native tree abundance in the smallest size class was unrelated to Ligustrum canopy dominance, while native tree abundance in larger size classes and native liana abundance were negatively correlated with Ligustrum dominance.  Native species composition was both environmentally and spatially structured, suggesting that some species are dispersal limited.  Seed rain was spatially correlated with conspecific basal area for one of two native species, but not for Ligustrum. Conclusions- Native tree recruitment appears to be limited primarily by sapling mortality in patches dominated by the invasive Ligustrum.  Ligustrum does not appear to be dispersal limited in our study area and is likely to continue spreading.  Invaded patches may persist for hundreds of years